THE IMPACT OF AI-ASSISTED SPEAKING APPLICATIONS ON EFL STUDENTS' ORAL FLUENCY AND CONFIDENCE - Imelda Kurniati; Lili Elisa Rahma; Nadhifa Shofi Andara; Didik Santoso (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The rapid development of Artificial Intelligence (AI) has introduced innovative language learning applications with the potential to improve English speaking skills. However, empirical evidence regarding students' perceptions of AI-assisted speaking applications, particularly their influence on oral fluency, confidence, speaking anxiety, and learning motivation, remains limited. Investigating these aspects is important because affective factors substantially influence the success of speaking performance among English as a Foreign Language (EFL) learners. This study aimed to examine students' perceptions of the impact of AI-assisted speaking applications on speaking performance and affective learning outcomes. A quantitative survey design was employed involving 15 undergraduate students from the English Education Program selected through purposive sampling. Data were collected using a structured four-point Likert-scale questionnaire and analyzed through descriptive statistics. The findings revealed that 86.7% of participants perceived AI applications as improving oral fluency, 80% reported increased speaking confidence, 86.7% experienced reduced speaking anxiety, and 86.6% indicated higher motivation to practice English independently. The study concludes that AI-assisted speaking applications are effective supplementary learning tools that enhance both speaking performance and learners' psychological readiness, supporting more autonomous and sustainable EFL learning. ABSTRAK Perkembangan teknologi Artificial Intelligence (AI) telah menghadirkan berbagai aplikasi pembelajaran bahasa yang berpotensi meningkatkan keterampilan berbicara bahasa Inggris. Meskipun demikian, penelitian mengenai persepsi mahasiswa terhadap pemanfaatan aplikasi berbasis AI, khususnya yang berkaitan dengan kelancaran berbicara, kepercayaan diri, speaking anxiety, dan motivasi belajar, masih relatif terbatas. Kajian ini penting karena aspek afektif dan psikologis berperan besar dalam keberhasilan pembelajaran berbicara pada pembelajar English as a Foreign Language (EFL). Penelitian ini bertujuan menganalisis persepsi mahasiswa mengenai dampak penggunaan aplikasi latihan berbicara berbasis AI terhadap kemampuan berbicara dan faktor-faktor afektif yang mendukung pembelajaran. Penelitian menggunakan pendekatan kuantitatif dengan desain survei terhadap 15 mahasiswa Program Studi Pendidikan Bahasa Inggris yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan kuesioner skala Likert empat poin dan dianalisis secara deskriptif menggunakan frekuensi dan persentase. Hasil penelitian menunjukkan bahwa 86,7% responden menyatakan AI membantu meningkatkan kelancaran berbicara, 80% melaporkan peningkatan kepercayaan diri, 86,7% merasa speaking anxiety berkurang, dan 86,6% menyatakan AI meningkatkan motivasi berlatih secara mandiri. Penelitian ini menyimpulkan bahwa aplikasi berbasis AI merupakan media pendukung yang efektif untuk meningkatkan keterampilan berbicara sekaligus memperkuat kesiapan psikologis mahasiswa dalam pembelajaran EFL.